Fermentation Processes: Modeling, Optimization and Control: 2nd Edition - Ricardo Aguilar López (Fermentation, 2025)
Fermentation is an important cornerstone of bioengineering, which plays a critical role in the production of a wide array of products including pharmaceuticals, biofuels, food additives, industrial chemicals and enzymes [...]